AN ADVENTURER WHO ASSERTED RIGHT ON THE OTTOMAN THRONE: PRETENDER PRINCE AHMED NADİR BEY - Musa KILIÇ (Fırat University, 2019)
As can be seen on the other dynasties, in the history of the Ottoman Empire some pretender princes claimed that they are one of the members of the sultanate family. Ahmed Nadir Bey who emerged in the late period of Mahmud II and claimed to be the son of Mustafa IV and the rightful heir of the sultanate, was one of these names. According to pretender prince’s story, after the abdication of his father his pregnant mother who was ordered to be killed but she could have managed to escape. Ahmed Nadir found out who he really was but after the death of his mother. Thenceforth, the only purpose of his life was to take revenge on his father. He worked under the command of the Ottoman Empire and the Viceroy of Egypt Kavalalı Mehmed Ali Pasha for a while. But he escaped to Europe for fear of letting on his secret. And then Ahmed Nadir tried to persuade the European governments about his claim. Although he was not seriously treated by the European goverments his story was sufficiently interesting to attract the attention of the European press and public. After then he fade away temporarily but in 1843, he resurfaced in Tarsus. He tried to induce local governors to raise a rebellion in Anatolia but the result was a complete dissappointment for Ahmed Nadir. After arrested by the Ottoman authorities he was sent first to Konya and then to İstanbul. There were a lot of rumours who he really was. But it was defined as a Polish refugee. On the other hand it could not have been completely understood why he attempted such a dangerous claim.